Hypomethylating agents plus venetoclax for high-risk MDS and CMML as bridge therapy to transplant: a GESMD study - Ines Zugasti; Monica Lopez-Guerra; Sandra Castaño-Díez; Daniel Esteban; Alejandro Avendaño; Helena Pomares; Ana Perez; Sara García-Ávila; Irene Padilla Conejo; Cristina de la Fuente Montes; Alexandra Martínez-Roca; Beatriz Merchán; et al. (Experimental Hematology & Oncology)
Abstract Background High-risk myelodysplastic syndromes (HR-MDS) and chronic myelomonocytic leukemia (CMML) remain therapeutic challenges with suboptimal outcomes. The only potentially curative treatment is allogeneic stem cell transplantation (allo-SCT). The most frequent pre-allo-SCT treatment is monotherapy with hypomethylating agents (HMA), but approximately 40% of patients cannot proceed to allo-SCT, mainly due to disease progression. Recent evidence suggests that combining HMA with venetoclax (HMA/VEN) could increase HMA efficacy in HR-MDS but it remains unclear if this combination could bridge more patients to allo-SCT. Methods We retrospectively evaluated HMA/VEN as a bridge to allo-SCT in 30 patients with HR-MDS or CMML eligible for transplant. Eighteen patients were treatment-naïve and 12 were refractory or relapsed (R/R). Results As defined by the IWG 2023 criteria, the overall response rate (ORR) was 90% and the composite complete response rate was 77%. For the R/R patients, ORR was 83%. The allo-SCT rate was 83%, and the allo-SCT rate of those patients treated exclusively with HMA/VEN without further bridge therapies was 76%. One- and two-year post-allo-SCT survival was 75% and two-year cumulative incidence of relapse was 30.5%. Follow-up of measurable residual disease identified some molecular relapses that were controlled with preemptive treatment. Conclusions Our findings indicate that HMA/VEN combination therapy shows promise as a bridging strategy to allo-SCT in HR-MDS and CMML.